2020
DOI: 10.1007/s13204-020-01330-0
|View full text |Cite
|
Sign up to set email alerts
|

TEOS and Na2SiO3 as silica sources: study of synthesis and characterization of hollow silica nanospheres as nano thermal insulation materials

Abstract: Hollow structured material (HSM) consisting of monodisperse hollow silica nanospheres (HSN) shows a promising potential for construction insulation due to its affordable cost and simple process. Yet the studies of high-yield and low-energy for the synthetic of HSN are still insufficient. This research reported the comparison of morphology and performance of synthesize HSN utilizing TEOS and Na 2 SiO 3 as silica source. The average yield of Na 2 SiO 3 -based samples can reach 93.75%, which is about 10 times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Suitable silica precursors include tetraethyl orthosilicate (TEOS), 31 51 tetramethyl orthosilicate (TMOS), 31 , 52 56 and sodium silicate. 20 , 33 , 34 , 57 − 60 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Suitable silica precursors include tetraethyl orthosilicate (TEOS), 31 51 tetramethyl orthosilicate (TMOS), 31 , 52 56 and sodium silicate. 20 , 33 , 34 , 57 − 60 …”
Section: Introductionmentioning
confidence: 99%
“…One study compared silica deposition onto polystyrene latex particles using either sodium silicate or TEOS as precursors. 34 Sodium silicate formulations led to patchy, non-uniform overlayers and tended to produce aggregates. On the other hand, TEOS led to relatively uniform silica coatings with minimal particle aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1,5 ] In previous works, low effective thermal conductivities were measured in a range from 20 up to 141 mW m −1 K −1 . [ 1,5a,e −g, 6 ] The reason for reduced thermal conductivity is assumed to be a significantly lower density associated with a reduced number of solid–solid interfaces and a reduced thermal conductivity via gas phase. [ 1 ] It has been shown that if a self‐assembled crystal made of hollow spheres deviates from the local order, the thermal conductivity is significantly reduced with decreasing pressure.…”
Section: Introductionmentioning
confidence: 99%